Proximity induced time-reversal topological superconductivity in Bi2Se3 films without phase tuning - Casas, Oscar E. (2019)
Many proposals to generate a time-reversal invariant topological superconducting phase are based on imposing a π phase difference between the superconducting leads proximitizing a nanostructure. We show that this phase can be induced on a thin film of a topological insulator like Bi2Se3 in proximity to a single s-wave superconductor. In our analysis we take into account the parity degree of freedom of the electronic states which is not included in effective Dirac-like surface theories. We find that the topological phase can be reached when the induced interparity pairing dominates over the intraparity one. Application of an electric field perpendicular to the film extends the range of parameters where the topological phase occurs.